Case Report: COVID-19-Associated ROHHAD-Like Syndrome - Artamonova, Irina N.; Petrova, Natalia A.; Lyubimova, Natalia A.; Kolbina, Natalia Yu; Bryzzhin, Alexander V.; Borodin, Alexander V.; Levko, Tatyana A.; Mamaeva, Ekaterina A.; Pervunina, Tatiana M.; Vasichkina, Elena S.; Nikitina, Irina L.; Zlotina, Anna M.; et al. (Frontiers in Pediatrics, 2022)
It is known that the SARS-Cov-2 virus may cause neurologic damage. ROHHAD syndrome (Rapid-onset obesity, hypoventilation, hypothalamus dysfunction, and autonomic dysregulation) is a disease of unknown etiology with a progressive course and unclear outcomes. The etiology of ROHHAD syndrome includes genetic, epigenetic, paraneoplastic, and immune-mediated theories, but to our knowledge, viral-associated cases of the disease have not been described yet. Here we present a case of a 4-year old girl, who developed a ROHHAD syndrome-like phenotype after a COVID-19 infection, and the results of 5-months therapy. She had COVID-19 pneumonia, followed by electrolyte disturbances (hypernatremia, hyperchloremia), hypocorticism and hypothyroidism, central hypoventilation, requiring prolonged assisted lung ventilation, bulimia, and progressive obesity with hypertriglyceridemia, dyslipidemia, hyperuricemia, hyperinsulinemia. Repeated MRI of the brain and hypothalamic-pituitary region with contrast enhancement showed mild post-hypoxic changes. Prader-Willi/Angelman syndrome, as well as PHOX2B-associated variants, were ruled out. Treatment with NSAID and monthly courses of IVIG led to dramatic improvement. Conclusion: Herein, the first description of ROHHAD-like syndrome is timely associated with previous COVID-19 infection with possible primarily viral or immune-mediated hypothalamic involvement.